The confluence of cultural attitudes and community empowerment: resident support for sustainable heritage tourism in Qufu, China - Liu, Yanying; Konar, Rupam; Subramaniam, Thanam; Kunasekaran, Puvaneswaran (Routledge, 2025)
Cultural heritage distinguishes itself from other tourist attractions because of its exceptional universal value, and empowerment plays a crucial role in advancing sustainable tourism development. In this context, this study aims to explore the direct and indirect relationships among residents’ cultural attitudes, community empowerment, their perceptions of sustainable cultural heritage tourism, and their support for such tourism. To achieve this, the partial least squares structural equation modeling (PLS-SEM) method was used to analyze data from 486 valid questionnaires collected in Lucheng Street, Qufu City. The results confirm that residents’ cultural attitudes, community empowerment, and their perceptions of sustainable cultural heritage tourism significantly influence their support for it. Specifically, positive perceptions were found to mediate the relationship between residents’ cultural attitudes and their support, as well as the relationship between community empowerment and support. Conversely, residents’ negative perceptions only mediated the relationship between community empowerment and support. These findings enhance site managers’ understanding of how to interpret and respond to residents’ attitudes. They also provide practical insights for improving community management systems, balancing cultural heritage preservation with tourism sustainability.